The impact assessment of automated drip infusion control using weighing scale and pinch method on subjects - Agustine, Lanny; Astarini, Made Indra Ayu; Manungkalit, Maria; Amadeus, Jose; Pranjoto, Hartono (E3S web of conferences, 2024)
A novel approach in infusion flow control technology under development is based on liquid weight and pinch valve control to stop and control the flow for better management. The main part of this device consists of a load cell, a microcontroller, and a pinch valve. In this method, a pinch valve controls the rate of infusion drops as prescribed to the patient, so that nurses do not have to keep on checking the infusion flow rate. The device detects the infusion flow from the measured liquid weight, which is mathematically converted to volume. A pinch valve, via a pinch-release method, controls the amount of fluid via the pinch duration. In this study, the effective duration of valve opening and the sensations of the fluid flow by the patients are also studied. The study, which involves fourteen healthy subjects, shows that a valve opening of a maximum of 70 ms is still considered comfortable. Some subjects indicate discomfort with pinch opening longer than 70ms. A valve opening of less than 70ms shows no significant impact on the increase of outflow volume with a pinch-release period of 3000ms. The increase in outflow volume is quite linear concerning the pinch valve opening period. With this method, the prescription is more accurate and will lessen the impact of medical waste for better environmental impact..